Has the Covid-19 pandemic jeopardized firms' environmental behavior? Bridging green initiatives and firm value through the triple bottom line approach - Karman, Agnieszka; Prokop, Viktor; Giglio, Carlo; Rehman, Fazal ur (Wiley-Blackwell, 2024)
The Covid-19 pandemic has caused a significant decline in stock markets worldwide, and organizations are experiencing serious financial problems. Protecting and preserving firm value are critical ways to help organizations survive the crisis. This study analyzes a sample of 45 firms listed on the Polish Stock Market in two periods to determine the relationship among green initiatives, the triple bottom line (TBL) perspective, and firm value in the periods before and during the crisis caused by the Covid-19 pandemic. The results show that firms with higher green initiatives are more likely to obtain better TBL performance during the normal period. Economic and social dimensions of TBL positively influence firm value regardless of the period, but the same is not true of the ecological dimension. The Covid-19 pandemic's negative impact on investors' perception does not translate to firm value. This study provides the first empirical evidence on the value of organizations affected by the Covid-19 pandemic in the context of environmental management. By considering the TBL approach, this study provides a new boundary condition that explains the impact mechanism of green initiatives during a crisis.
Ohrozila pandemie Covid-19 environmentální chování firem? Spojení zelených iniciativ a pevné hodnoty prostřednictvím přístupu trojího zisku
Keywords: Covid-19; green initiatives; TBL approach; value; COVID-19; zelené iniciativy; TBL přístup; hodnota